Carbon Dioxide Sequestered Concrete - Mohd Kamal, Nur Liyana; Itam, Zarina; Sivaganese, Yuovendra; Abdul Razak, Norizham (International Journal of Integrated Engineering, 2020)
Carbon dioxide, CO2accounts for most of the emission from all the types of greenhouse gasses in the whole world. The ability of CO2to remain longer than other greenhouse gases and the convenience of producing CO2has resulted in its high projection in a yearly manner. The prime factor for the emission of CO2are from the actions of human beings. One such human act is the concrete industry. Total emissions from the concrete industry could therefore contribute as much as 8% of global CO2emissions. Sequestered CO2in concrete can provide an impact on reducing the carbon footprint and also is able to improve the compressive strength of concrete. During this process, the sequestered carbon dioxide chemically reacts with cement to produce a mineral, trapping the carbon dioxide gas in the concrete. Hence, sequestering the carbon dioxide gas in concrete does not only on a bigger scale, reduce carbon footprint but also reduces the impact the construction industry has on the environment. This paper presents a detailed review on the chemical reaction that takes place during the sequestration of carbon dioxide and the research published on the effects of carbon dioxide sequestered concrete on its properties. The impact this process has on the concrete industry and the environment is discussed in this paper.